Imagology of Iranians in One Thousand Nights and One Night (European Journal of Language and Literature, 2016)
Imagology is a branch of comparative literature which explores the image of one nation in the literature of another nation. One Thousand Nights and One Night is among the important books which can show the image of different nations and people such as Indians, Iranians and Arabs. Since the oldest version of the book is in Arabic, it is considered an Arabic literary work though it was translated from a Persian tale in the first place. On this basis the study of the image of Iranians in One Thousand Nights and One Night can be included under the definition of imagology. In this article, first we explain, analyze and study the image of Iranians in the book One Thousand Nights and One Night with respect to 1. anthropology (including entertainments, personification of animals, disapprobation of lies and betrayal of spouses), 2. religious and mythical beliefs (including the belief in daevas and jinnis, magic, fire-worshipping and similar plots), 3. politics (emphasizing the position of vizier and his family in government), 4. economics (emphasizing economic prosperity), then we will compare the collected information with the image of Iranians in credited works and in this way we will identify the similarities and differences of Iranians’ image in One Thousand Nights and One Night and the above-said literary works. Finally we come to this conclusion that the similarities belong to the real image of Iranians in the pre-Islamic days and that differences show the image of post-Islamic Iran which is added through Arabic translation.